The lifetime financial plan the seven ages of financial health - Oliver, Jack (Financial Times Pitman Pub., 1998)
"It is indeed very rare to find a book which can act as a standard work for the new entrant to our business, the experienced practitioner and also the consumer. Jack Oliver's book is not only that rarity. It is an exceptional book. Why? In taking seven stages in our lives, with which all the readers will identify, the recommendations for financial planning at each stage are, like the book itself, irresistible." - Leonard J. Warwick, CBE ALIA (dip), MIFP, Chairman, Personal Investment Authority Training Advisory Group, Director of the Securities and Investments Board (SIB) 1989-96 "There is something for everyone in this book. Jack Oliver provides detailed and comprehensive advice and information to cover virtually every financial contingency - all of which is presented in a clear and accessible way." - Dr. Andrew Sentance, Chief Economist, British Airways, a former member of the Treasury Panel of Independent Forecasters, the 'seven wise men,. "This is a superb book which deals with life from the cradle to the grave. Excellent case-studies and complex matters dealt with in a simple and readable way. I recommend all people involved in the sale of financial products to keep a copy of this publication very handy as a great reference help." - Frank Weisinger, FLIA, MLIA (dip), President of the Life Insurance Association during its Silver Jubilee, 1996-7. "It,s a pity this excellent book was not available to me forty years ago, but I'm glad to say it's not too late for me to benefit from the last two chapters - on retirement and old age!" - Professor Patrick Dowling, FEng FRS, Vice-Chancellor and Chief Executive, University of Surrey. "A clear concise guide to a lifetime of financial planning, providing a perfect reference. A must for those who wish to conduct their own affairs, highly recommended." - Colin M Hart MLIA (dip), National Chairman of Training and Competence, Life Insurance Association. Today, enjoying financial health depends more than ever on planning for your financial future, but it isn't easy to predict what is going to happen in the years ahead. With each new age comes new challenges and opportunities. How can you make financial plans to best suit your current situation? Which plans and investments will also meet your needs in the ages of your life yet to come? How can you evaluate your own requirements before consulting an adviser or selecting an investment? As a financial planning consultant with 'all ages, of experience, Jack Oliver can help you to plan for a financially healthy future. Take responsibility for your own financial planning The Lifetime Financial Plan is an interactive companion to successful financial planning for the 7 ages of financial health: *birth and education: developing the habit of saving money; comparison of the different investments which could be used; budget keeping. *work: contract of employment and redundancy cover; what happens if I become medically unable to work?; early planning for financial independence; pensions including state provision. *marriage: financial planning together; buying a home; a comparison of all types of mortgage and the vehicles for repaying them; intestacy and wills. *parenthood: ensuring the financial security of children; writing policies in trust; funding private education. *career development: the successful employee and his career package; building an investment portfolio, running your own business; capital gains tax in detail; all types of pension and using them to the best advantage. *retirement: safeguarding the pension and maximising its return; inheritance tax and passing on as much of your estate as possible. *old-age: the most efficient way of providing long-term care, if needed; saving plans for grandchildren. These 7 core sections can be used to build flexible and customised solutions suitable for you or your family's financial needs. Written in an accessible style, this book combines financial instruments with worked examples, case studies and exercises which highlight the investment strategies that will really work for you. Author: Dr Jack Oliver, Bsc, PhD, C.Math, FIMA, MLIA (dip), FPC, Financial Planning Consultant Becoming a financial planning consultant after a university career lecturing in mathematics and the psychology of learning mathematics, Jack Oliver brought his own special expertise to his new profession. He combines an extensive technical knowledge with the ability to impart that knowledge to others. Proud of the financial planning he gives, his clients range from the very young to those on retirement; from barristers and senior executives to nurses and teachers. With this book, he is passing on his knowledge to you.